2020
DOI: 10.33736/ijbs.3275.2020
|View full text |Cite
|
Sign up to set email alerts
|

Implications of ICT for Development on Enhancing Rural Entrepreneur Program (REP) at Telecentres in Malaysia

Abstract: This paper examines rural social entrepreneurship program in rural Malaysia communities. The program seeks to promote and turn rural entrepreneurs into social entrepreneurs by strengthening their economic activities and enhancing social capital. This paper focuses on a component of the rural entrepreneur program (REP), namely the Social Entrepreneur Club (SEC). The club runs the rural entrepreneur program and upholds the program’s objectives. It promotes the socialization of rural communities by engaging them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…A study on communities in Semarang, Central Java province, determined communities is the main actors in community empowerment [16]. Telecentre was used to improve the economic level in Western Cape, South Africa [17] ICT facilities at the telecentre improve the rural community's quality of life [18]. Various activities are provided at community internet centers, such as computer skill classes, English language classes, online business management, cooking class, basic health check, and many appropriate activities.…”
Section: B Community Empowerment In Rural Areasmentioning
confidence: 99%
“…A study on communities in Semarang, Central Java province, determined communities is the main actors in community empowerment [16]. Telecentre was used to improve the economic level in Western Cape, South Africa [17] ICT facilities at the telecentre improve the rural community's quality of life [18]. Various activities are provided at community internet centers, such as computer skill classes, English language classes, online business management, cooking class, basic health check, and many appropriate activities.…”
Section: B Community Empowerment In Rural Areasmentioning
confidence: 99%
“…Inadequate funding is a serious issue that negatively impacts the sustainability of telecentres (Gcora et al, 2015). In Malaysia, Noor (2021), reported that inadequate funding has been a problem for telecentres in Malaysia, which has negatively impacted their capacity to buy essential ICT resources and other resources. Stakeholders have raised the idea of privatization as a solution to the financial difficulties these telecentres confront.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The facilities further increases access to educational information through the provision of internet services to teachers, parents, recent graduates, and the community at large (Hoq, 2015). Information obtained through telecentres, enhances people's literacy levels, in both traditional and digital environments, as well as improving their ability to make informed decisions and effectively participate in society (Chege et al, 2019; Chikumba, 2011; Furuholt & Sæbø, 2018; Noor et al, 2020). Considering the educational benefits offered by the telecentres, people still patronize the telecentres in this age of mobile technology to acquire information that may enable them to achieve their educational goals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation